Granular Synthesis - Gelatin : La Biennale di Venezia 2001 - Österreichischer Pavillon. - Druckrey, Timothy; Fassler, Manfred; Medalla, David; Pursel, Dick; Schweeger, Elisabeth (Ostfildern-Ruit : Hatje Cantz Verlag, 2001)
Granular Synthesis are pioneers of the audio-visual media, who, for ten years now, have dedicated themselves to the fusion of sound and image and who have translated it into a coherent medium. As an essential part of their artistic practice, they develop relevant software. They compile hardware configurations that enable them to play video as an intuitive instrument. With their almost symphonic performances and installations Granular Synthesis build electronic emotion machines, which encircle the public, overwhelm, attack and affect the senses.
gelatin create life models, which allude directly to a place, refer to it and stake no claim to eternity. In its frequently performative, subversive dispute, the access to corporality as an architectonic element plays an essential role, bodies create places, create communication, self-confidence - body is space. Their works convey the possibility of a reflection about the immediate and necessary experience of artistic processes. The interactive process plays an inherently essential role in this.
Duits & Engels
Granular Synthesis - Gelatin, La Biennale di Venezia : pav. Oostenrijk,06. t/m 11.2001
kunstcatalogus
Keywords: Granular Synthesis; Gelatin; Oostenrijk